Police Intervention in Corruption Prevention: Police and Community Synergy in Improving the Anti-Corruption Character of Students at Tlogodepok Mirit Kebumen - Surip, Surip; Arifin, Ridwan; Widyawati, Anis; Rasdi, Rasdi; Adiyatma, Septhian Eka (Advances in Police Science Research Journal, 2021)
.